O1-S04.04 Predictors of repeat Chlamydia trachomatis and/or Neisseria gonorrhoeae infections among African-American adolescent females. (10th July 2011) - Swartzendruber, A; DiClemente, R; Sales, J; Brown, J L; Rose, E
Abstract : Background: Young African-American females have the highest rates of Chlamydia (CT) and gonorrhoea (GC) in the US. Few studies have explored predictors of repeat STDs among this population. The objective was to identify predictors of repeat CT and/or GC infections among African-American adolescent females positive for at least one of these STDs at baseline. Methods: Sociodemographic, psychosocial and sexual behaviour data were collected via ACASI at baseline and every 6 months for 2 years from 701 African-American females (15–19 years) enrolled in an HIV prevention trial. Vaginal swabs were self-collected at each visit and assayed for CT and GC using DNA amplification. Participants with a positive test result received directly observable single-dose antimicrobial treatment and risk-reduction counselling. Repeat infection was defined as a positive test result following a negative result or documented treatment. Among those who tested positive for CT and/or GC at baseline, bivariate and multivariable analyses compared study variables for those who did vs did not have a repeat infection during the 2-year follow-up. Results: Of 615 (88%) participants with ≥1 follow-up test result, 122 (20%) had a positive CT and/or GC test result at baseline; 49 (40% of baseline positives and 8% of total) had a repeat infection during the study period. Of those with a repeat infection, 30 (61%) were positive at only one follow-up visit, 18 (37%) at two and 1 (2%) at three follow-up visits. In bivariate analyses, relative to those positive at baseline only, participants with repeat infection were less likely to have a boyfriend (71 vs 83%, p=0.043) and see themselves marrying their current boyfriend (57.1 vs 76.2%, p=0.05) and more likely to have had sex with a man who had sex with other men (8.2 vs 0%, p=0.013). Participants with repeat infection had higher mean impulsivity scores (p=0.027). Controlling for age and treatment assignment, greater impulsivity (AOR: 1.1, p=0.018) was associated with increased likelihood of a repeat infection and having a boyfriend (AOR: 0.21, p=0.006) with decreased likelihood of a repeat infection. Conclusions: Repeat CT and/or GC infections are common among African-American adolescent females. Among young African-American females who test positive for CT and/or GC, tailored interventions for more impulsive adolescents and those without a boyfriend may help prevent repeat infections.